2014
DOI: 10.1002/stem.1536
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Podocalyxin Separates the Hematopoietic and Vascular Potentials of Mouse Embryonic Stem Cell-Derived Mesoderm

Abstract: In the mouse embryo and differentiating embryonic stem cells, the hematopoietic, endothelial and cardiomyocyte lineages are derived from Flk1+ mesodermal progenitors. Here we report that surface expression of Podocalyxin (Podxl), a member of the CD34 family of sialomucins, can be used to subdivide the Flk1+ cells in differentiating embryoid bodies at day 4.75 into populations that develop into distinct mesodermal lineages. Definitive hematopoietic potential was restricted to the Flk1+Podxl+ population, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Additional studies have identified markers to differentiate between hemangioblast and hemogenic endothelium, such as cell-surface intercellular adhesion molecule 2 (ICAM2) (Pearson et al, 2010) and the Ets-related protein encoding transcription factor ETV2 (Wareing et al, 2012). Other molecules such as podocalyxin (Zhang et al, 2014) have been shown to distinguish primitive from definitive hematopoietic potentials.…”
Section: The Next Step: How Observations In Yolk Sac Hematopoiesis Camentioning
confidence: 99%
“…Additional studies have identified markers to differentiate between hemangioblast and hemogenic endothelium, such as cell-surface intercellular adhesion molecule 2 (ICAM2) (Pearson et al, 2010) and the Ets-related protein encoding transcription factor ETV2 (Wareing et al, 2012). Other molecules such as podocalyxin (Zhang et al, 2014) have been shown to distinguish primitive from definitive hematopoietic potentials.…”
Section: The Next Step: How Observations In Yolk Sac Hematopoiesis Camentioning
confidence: 99%
“…Zhang et al [30] showed that podocalyxin (podxl) expression separates the hematopoietic and cardiac potential of mouse ESC‐derived Flk1 + mesoderm. Flk1 + cells expressing podxl showed definitive hematopoietic potential, and Flk1 + cells lacking podxl gave rise to cardiomyocytes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [30] showed that podocalyxin (podxl) expression separates the hematopoietic and cardiac potential of mouse ESC‐derived Flk1 + mesoderm. Flk1 + cells expressing podxl showed definitive hematopoietic potential, and Flk1 + cells lacking podxl gave rise to cardiomyocytes [30]. Their results, combined with our data, would indicate that the characteristics of F + podxl + cells and F + podxl − cells resemble those of F + C − cells and F + C + cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of Podxl’s actions have predominantly focused on renal podocytes, in which Podxl is important for podocyte foot extension and glomerular diaphragm slit formation [3]. Podxl has also been implicated in supporting vascular integrity [4], and its co-expression with Flk1 distinguishes embryonic Flk1 pos Podxl neg endothelial precursor mesodermal cells from definitive Flk1 pos Podxl pos hematopoietic progenitors [5]. Podxl additionally can mark sub-populations of embryonic CD34 pos hematopoietic stem cells [6], and Podxl/Pclp1 has been defined as functional marker of hematopoiesis within AGM regions [7].…”
Section: Introductionmentioning
confidence: 99%